Building school health partnerships to improve pediatric asthma care: the School-based Asthma Management Program. Issue 2 (April 2017) - Kakumanu, Sujani; Antos, Nicholas; Szefler, Stanley J.; Lemanske, Robert F.
Abstract : Purpose of review: Children with asthma require care that is seamlessly coordinated so that asthma symptoms are recognized and managed at home and at school. The purpose of this review is to discuss recent consensus recommendations in school-based asthma care. Recent findings: The School-based Asthma Management Program (SAMPRO) provides a widely endorsed framework to coordinate care with schools and consists of four components: establishing a circle of support around the child with asthma; facilitating bidirectional communication between clinicians and schools; comprehensive asthma education for schools; and assessment and remediation of environmental asthma triggers at school. SAMPRO standardizes recommendations for school-based asthma care coordination and provides a toolkit with websites and resources useful for the care of children with asthma in the school setting. Summary: The review will discuss the need for coordinated school asthma partnerships, the inception and development of SAMPRO, and its vision to improve pediatric asthma care coordination within the circle of support, comprising clinicians, school nurses, families, and communities.